2014
DOI: 10.1111/eff.12157
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal habitat choice, environment and spatial distribution of juveniles on their propensity for anadromy in a partially anadromous population of rainbow trout (Oncorhynchus mykiss)

Abstract: This study evaluated the importance of the environment and spatial distribution of juvenile fish for the adoption of alternative migratory tactics in a partially anadromous population of rainbow trout (Oncorhynchus mykiss) from the Santa Cruz River. We captured young-of-the-year fish along the river during autumn 2009, 2010 and spring 2010 and determined their maternal origin (anadromous vs. resident) using strontium to calcium ratios in the otolith core. Relative proportion of anadromous offspring, modelled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…There appear to be correlations between the prevalence of anadromy and residency and physical features of river drainages, including drainage size (McPhee et al 2014), stream channel complexity (e.g., Pavlov et al 2001a) and depth (Liberoff et al 2014b), and the presence of lakes (e.g., Russell 1974). These habitat features likely influence and are correlated with several other parameters (e.g., food and temperature), so it is difficult to untangle the specific effects of any single factor.…”
Section: Stream Geomorphology and The Role Of Lakesmentioning
confidence: 99%
“…There appear to be correlations between the prevalence of anadromy and residency and physical features of river drainages, including drainage size (McPhee et al 2014), stream channel complexity (e.g., Pavlov et al 2001a) and depth (Liberoff et al 2014b), and the presence of lakes (e.g., Russell 1974). These habitat features likely influence and are correlated with several other parameters (e.g., food and temperature), so it is difficult to untangle the specific effects of any single factor.…”
Section: Stream Geomorphology and The Role Of Lakesmentioning
confidence: 99%
“…(). Therefore, the higher nutritional status displayed by anadromous progeny in early stages, coupled with the adequate physical environment determined by maternal spawning site selection (Liberoff et al ., ), might play an important role in the adoption of the anadromous tactic in this population.…”
Section: Multiple Regression Model Explaining Oncorhychus Mykiss Lipimentioning
confidence: 96%
“…Offspring of anadromous mothers are more likely to become anadromous because they grow faster and achieve a larger size than resident offspring (Liberoff et al ., ). In addition, maternal spawning behaviour determines juvenile rearing habitats providing the adequate physical environment for anadromous offspring to achieve larger body sizes and become anadromous (Liberoff et al ., ).…”
Section: Multiple Regression Model Explaining Oncorhychus Mykiss Lipimentioning
confidence: 97%
See 1 more Smart Citation
“…One study at the stream network scale in the John Day River Drainage in Oregon indicated that stream size influences the frequency of anadromy (Mills et al 2012). Increasing residency in O. mykiss with distance upstream has been observed widely (e.g., McMillan et al 2007), but in at least one case, the opposite trend has been observed (Liberoff et al 2015). The influence of distance per se can be difficult to distinguish from other environmental factors.…”
Section: Acknowledgmentsmentioning
confidence: 99%